PENGARUH POLA MAKAN DAN KEPATUHAN IBU HAMIL MENGKONSUMSITABLET ZAT BESI TERHADAP KADAR HEMOGLOBIN DIKECAMATAN TARUTUNG KABUPATENTAPANULI UTARA TAHUN 2017 - Nurlela Mariana Nababan (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2018)
Haemoglobin level is the measuring of pigmenrespiratoricin red blood cells. Mothers’ haemoglobin level effect the weight of the baby. The pregnant women with low Haemoglobin level will danger the mothers and the babies. It is caused by the less of nutrition supply and oxygen to the placenta and effect the function of placenta for the fetus. This is an observasional analitic study with cross sectional approach. This study is aimed to find out the effect of mothers’ eating pattern and the obidience of consuming Fe tablet to the haemoglobin level in Puskesmas Hutabaginda Kabupaten Tapanuli Utara.The population is all pregnant women who examined their pregnancy and got Fe tablet in Puskesmas Hutabaginda Kecamatan Tarutung in 2017 around 60 persons, and they become the samples. The data were collected by questionaire ans interview. The data were analyzed usingunivariate, bivariate, and multivariate. The result of the study show that there is effect between eating pattern pattern and haemoglobin level with p value = 0,000, and there is effect between mothers’ obidience in consuming Fe tablets and haemoglobin level with p value = 0,000. He most effected variable is the mothers’ obidience in consumingg Fe tablet (p = 0,000; OR = 17,6). It means that the mothers who don’t consume the Fe tablet regularly have the risk17,584 bigger to have low haemoglobin level than the mothers who consume regularly. Therefore it is suggested to the Puskesmas Tarutung staff to give counselling about eating pattern and the obidience of consuming Fe tablets so the pregnant women and the babies will be healthy.